Solubilization of natural phosphates by microorganisms isolated from Pinus and Eucalyptus plantations in Santa Catarina, Brazil - Filho, Germano Nunes Silva; Narloch, Charles; Scharf, Rosana (Pesquisa Agropecuaria Brasileira, 2002)
The use of P-solubilizing microorganisms have been suggested as an alternative to replace the utilization of phosphate fertilizers. In order to be used in programs of controlled inoculation, microorganisms must display a high capacity and potential for solubilization. The aim of this study was to evaluate the potential and the capacity of 56 microbial isolates to solubilize different types of phosphates. The evaluation was performed in GES medium supplemented with one of the following phosphates: Anitápolis, Araxá and Catalão, through a factorial experiment [(56 isolates + control) x three phosphates] in a randomized complete design with three replications. After 15 days of inoculation, levels of phosphorus and pH of the media were determined. Effects of phosphates, isolates and the interaction were verified. Low values of pH were obtained by isolates with high and medium potential. The average level of P was superior in Anitápolis phosphate, followed by Araxá. Thirty-one isolates solubilized significant quantities. The isolate 310 showed the highest potential (average of 263 mg mL-1 of P). Four isolates (177, 262, 252 and 269) showed high potential (120 to 150 mg), and twelve (201, 309, 199, 195, 249, 202, 198, 305, 253, 196, 203 and 307) showed medium values (80 to 120 mg). Isolates behavior was different among phosphates. Only four isolates solubilized all three phosphates (310, 251, 199 and 249). The characteristics displayed by isolates 310, 251, 199 and 249 qualified them for a screening program aiming controlled inoculation.